Poverty alleviation model in communities peatland areas of Jambi Province. Issue 1 (March 2021) - Wahyuni, I; Suandi; Edison
Abstract: This research was aimed to analyze the poverty alleviation model in communities peatland areas of Jambi Province. The research design was a cross-sectional and conducted in two selected districts in Jambi Province, namely: Tanjung Jabung Timur and Tanjung Jabung Barat Districts. This research was conducted from July to December 2018. Data collection was carried out by writing a structured questionnaire consisting of family characteristics, family income, social capital, and household resource management. The number of respondents was 180 households, which was taken by simple random sampling. The data collected will be tested with a descriptive approach and SEM with the Linear Structural Relationship (LISREL) program. The results showed that the income of the community in the peatland area of Jambi Province was Rp. 4, 781, 000, 000, - or income sufficiently. The results of the analysis show that social capital and family resource management have a positive and significant effect on food security and poverty alleviation. Therefore, the poverty alleviation model in peatland areas is by utilizing social capital resources and managing family resources.